Role of DNA-dependent protein kinase in neuronal survival. - Chechlacz, M; Vemuri, M; Naegele, JR (2001)
DNA-dependent protein kinase (DNA-PK) is a DNA repair enzyme composed of a DNA-binding component called Ku70/80 and a catalytic subunit called DNA-PKcs. Many investigators have utilized DNA-PKcs-deficient cells and cell lines derived from severe combined immunodeficiency (scid) mice to study DNA repair and apoptosis. However, little is known about the CNS of these mice. This study was carried out using primary neuronal cultures derived from the cerebral hemispheres of new-born wild-type and scid mice to investigate the effects of loss of DNA-PK function on neuronal maturation and survival. Purified neuronal cultures developed comparably in terms of neurite formation and expression of neuronal markers, but scid cultures showed a significant increase in the percentage of dying cells. Furthermore, when apoptosis was induced by staurosporine, scid neurons died more rapidly and in higher numbers. Apoptotic scid neurons exhibited nuclear condensation, DNA fragmentation and caspase-3 activation, but treatment with the general caspase inhibitor, N-benzyloxycarbonyl-Val-Ala-Asp-(O-methyl) fluoromethyl ketone did not prevent staurosporine-induced apoptosis. We conclude that a DNA-PK deficiency in cultured scid neurons may cause an accumulation of DNA damage and increased susceptibility to caspase-independent forms of programmed cell death.